Корпоративниот бренд како извор на одржлива конкурентска предност на компаниите - Веселинова, Елена (Економски факултет, УКИМ, Скопје, 2014)
The main reason for the stressed actuality of the corporate brand as a source of competitive advantage lies in the fact that in the long run there is no other alternative but to be better than the competition. To win and retain this position companies ought to demonstrate superior qualities against their competitors in many different ways. The common denominator for the superiority of one company over others is exactly the value of its corporate brand, measured through different attributes. Companies are permanently faced with two eternal categories: complexity and variability. The process of building and managing the corporate brand enables dynamic development of companies through time and space along with the successful confrontation with problems arising from the above categories. The research subject of this doctoral dissertation is the importance of the corporate brand for long-term companies’ profitability, primarily in R. Macedonia, and then globally, taking into account the complexity of the environment as a resultant factor that increasingly complicates the process of creating new value and its effectuation in stable profitability. The thesis analyzes the question whether the sustainable source of competitive advantage derives from emphasis of the internal strengths and the elimination of internal weaknesses or it is the result of successful manipulation with the opportunities in the environment and avoidance of external threats. Despite the efforts of numerous authors supporting the second, the modern scientific thought in the field of strategic management emphasizes the first variant. So, the analysis of intangible resources and their mobility as a necessary condition for sustainable competitive advantage follows as a logical sequence. Thus, the idea of the corporate brand as a sublimate of all typical resources and capabilities of the company is being analyzed, which results in the creation and maintenance of the desired competitive advantage. This thesis is proved through the prism of the VRIO concept. Furthermore, the thesis analyzes the phenomenon of branding companies and the related process of creating new value, and thus sustainable competitive advantage. The arguments support the role of the corporate brand in providing greater market share, creating entry barriers for new competitors, achieving product and market expansion, providing premium price, attracting quality workforce, ensuring customer loyalty and stimulating innovation. This leads towards the analysis of the relationship of the so-called strategic stars: vision, culture and image of the company as a necessary condition for building and managing the corporate brand. At the core of the thesis is the corporate brand pentagon: rise, definition, articulation, measurement and expansion of the corporate brand. The model is a compilation of recognized models from authors famous worldwide and is globally validated by major corporations. The practicality of the model is proved by establishing the corporate brand equity: consumers’ awareness about the corporate brand, the level of the perceived quality of products / services, which associations the corporate brand awakes and how high the consumers’ loyalty to the brand is. The justification of all theoretical and practical knowledge in this dissertation is verified through the evaluation of the corporate brand. It is elaborated through several variants: the brand equity as a measure of the value of the brand, financial approaches to valuing corporate brands, integrating finance and marketing through the "best practice" approach, the value chain of the corporate brand and the return on investment in the corporate brand. In this way, the efforts for understanding, application and evaluation of the corporate brand as a source of competitive advantage are rounded. The conclusions systematize the observations and findings from the doctoral thesis in order to complete the analysis of the corporate brand as a source of competitive advantage for companies, which will strengthen the answer to the most essential question in economics: how to achieve more?
The corporate brand as a source of sustainable competitive advantage of companies
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: corporate brand, competitive advantage, brand equity, value creation, brand strategy